Heart rate and blood pressure control in obesity – how to detect early dysregulation?. (16th February 2015) - Javorka, Michal; Turianikova, Zuzana; Tonhajzerova, Ingrid; Lazarova, Zuzana; Czippelova, Barbora; Javorka, Kamil
Summary: Obesity is accompanied by many severe complications including various cardiovascular disorders. An impairment of cardiovascular control by autonomic nervous system could be one of the possible links between obesity and cardiovascular complications development. The aim of this study was to compare spontaneous heart rate and systolic blood pressure oscillations reflecting cardiovascular autonomic control of young obese subjects with normal control subjects by linear and nonlinear methods and to find sensitive markers of early autonomic dysregulation. Continuous recordings of beat‐to‐beat systolic blood pressure and RR intervals from ECG were obtained from 40 obese subjects (25 female, age 14·2 [13·1–16·1] (median [interquartile range]) years) and gender and age matched non‐obese control subjects. In addition to linear measures (time and frequency domain), we performed recurrence quantification analysis (RQA) and multiscale entropy analysis for both signals. While no significant differences in heart rate and systolic blood pressure dynamics were detected by linear measures and MSE, analysis of recurrence plots from RR intervals time series showed significant differences – indices trapping time and maximal length of vertical from RQA were significantly higher in obese compared to control group. We conclude that heart rate and blood pressure control by autonomic nervous system in young obese subjects is relatively well preserved. However, novel RQA‐related measures are able to detect early subtle abnormalities in cardiac autonomic control in obese subjects indicating decreased signal complexity.